Use of Lateral Access in the Treatment of the Revision Spine Patient - Samuel S. Bederman; Vu H. Le; Sohrab Pahlavan; Douglas P. Kiester; Nitin N. Bhatia; Vedat Deviren (The Scientific World Journal)
With the rate of spinal surgery increasing, we have seen a concomitant increase in the number of revision cases. It is, therefore, important to have a systematic approach to the management of these complicated patients with unique problems. A thorough understanding of the different pathologies affecting revision spine patients is critical to an effective treatment recommendation. Lateral access is a useful management approach since it can avoid the complications of operating through previous approaches. Furthermore, it possesses certain advantages for treatment in specific circumstances outlined in this paper. Long-term studies are needed to demonstrate the safety and efficacy of the lateral approach compared to the anterior and posterior approaches in the treatment of revision spine patients.